Communication competence in the activities of law enforcement institutions - Augustė Taraskevičiūtė; Rasa Dobržinskienė (Mokslo Taikomieji Tyrimai Lietuvos Kolegijose)
The article aims to investigate and assess communication competence in law enforcement by creating a clear understanding of current challenges, possible ways of improvement, and means of increasing the effectiveness of professional interaction. To achieve this aim, the following objectives were set: to discuss the concept of communication competence, review the theoretical aspects of communication competence in law enforcement, and investigate the peculiarities of communication competence in law enforcement institutions. The analysis of the scientific literature has shown that, in a general sense, competence is the ability of a person with self-organisation skills to act in an organised and purposeful way. Professional communication consists of specific aspects that are related to professional competencies. In law enforcement, communication is an essential part of law and order and public safety. Basic principles such as humanness, professionalism, clarity, confidentiality, trust, and proportionality ensure effective performance. Law enforcement officers need not only in-depth professional knowledge but also effective communication skills. Communication is legally regulated by codes of ethics, public relations legislation, and professional standards. Constant public criticism increases the pressure on institutions to communicate effectively and be accountable. The study shows that strong communication and cooperation skills are essential in law enforcement. The right management attitude, collaborative management, legal education, and specific rules are all components of mandatory communication competence. For law enforcement officers, it is not only knowledge that is important but also the ability to communicate safely and tactfully. Law enforcement communication is important for public safety, reputation, and transparency. The study showed a lack of expertise, particularly in relation to new technologies and emotional management. By promoting continuous improvement, cooperation with partners, and devoting more resources to improving communication skills, law enforcement institutions can serve the public more effectively.